2005
DOI: 10.1152/ajpendo.00442.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone inhibits the amplification of glucocorticoid action in adipose tissue

Abstract: Dehydroepiandrosterone (DHEA) exerts beneficial effects on blood glucose levels and insulin sensitivity in obese rodents and humans, resembling the effects of peroxisome proliferator-activated receptor-gamma (PPARgamma) ligands and opposing those of glucocorticoids; however, the underlying mechanisms remain unclear. Glucocorticoids are reactivated locally by 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), which is currently considered as a promising target for the treatment of obesity and diabetes. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 63 publications
(70 reference statements)
7
75
0
2
Order By: Relevance
“…DHEA significantly lowered 11␤-HSD1 mRNA expression in liver (19 Ϯ 3% of control; P Ͻ 0.001), WAT (28 Ϯ 5%; P Ͻ 0.001), and kidney (57 Ϯ 10%; P Ͻ 0.01; Figure 4), in line with previous observations in C57BL/6J mice. 17 DHEA treatment for a relatively short time (12 d) did not significantly alter food intake or body weight in C57BL/6J mice and Sprague-Dawley rats (data not shown). Figure 2.…”
Section: Dhea Modulates Glucocorticoid Metabolism By Inducing a Switcmentioning
confidence: 91%
See 3 more Smart Citations
“…DHEA significantly lowered 11␤-HSD1 mRNA expression in liver (19 Ϯ 3% of control; P Ͻ 0.001), WAT (28 Ϯ 5%; P Ͻ 0.001), and kidney (57 Ϯ 10%; P Ͻ 0.01; Figure 4), in line with previous observations in C57BL/6J mice. 17 DHEA treatment for a relatively short time (12 d) did not significantly alter food intake or body weight in C57BL/6J mice and Sprague-Dawley rats (data not shown). Figure 2.…”
Section: Dhea Modulates Glucocorticoid Metabolism By Inducing a Switcmentioning
confidence: 91%
“…17 Here, we tested the hypothesis that DHEA has antiglucocorticoid effects by inducing a switch from 11␤-HSD1-dependent activation to 11␤-HSD2-dependent inactivation of glucocorticoids. We investigated the impact of DHEA on 11␤-HSD2 expression and activity in RCCD2 rat cortical collecting duct cells.…”
Section: Dhea Upregulates 11␤-hsd2 Expression and Activity In Renal Cmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has properties to increase insulin sensitivity in hepatocytes (25). In addition, it has been shown that DHEA can inhibit 11β-hydroxysteroid dehydrogenase 1 expression in liver and adipose tissues (26). It is proposed that the overexpression of 11β-hydroxysteroid dehydrogenase 1 in adipose tissues increases the local cortisol production and thereby leads to the metabolic syndrome-like status (27,28).…”
Section: Discussionmentioning
confidence: 99%